Career Development of Functional Position of Customs and Excise Inspector At The Directoreate General Of Customs and Excise, East Jawa I Regional Office - Wisnuaji Purnomo (Universitas Airlangga, 2022)
The mandate of the ASN Law shows that the career development of the State Civil Apparatus is an integral part of ASN Management. The purpose of ASN career development is to match the needs and goals of existing employees, with the career opportunities available in the organization concerned. The function of ASN as Public Policy Executor as well as the glue and unifier of the nation requires ASN to have professional and high-performing skills, knowledge and attitudes. One way to achieve this is by choosing a career as a functional official.Directorate General of Customs and Excise (DGCE) as one of the government agencies under The Ministry of Finance of Indonesian Republic that serves the public in the field of customs and excise, also has a functional position in the structure of its employee positions. Based on the data of Directorate General of Customs and Excise strategic plan (Renstra) 2015-2019, DGCE still needs additional new employees as many as 8,298 people, among them from the side of internal factors, among others, to recruit Functional Officials of Customs and Excise Inspectors sub-elements of Customs Audit. In terms of aspects of career management, one of the activities carried out is to appoint and improve the management of functional positions of DJBC. This research is a descriptive qualitative research design in the form of a case study. The selection of the case study research design was based on the fact that the researcher wanted to clarify the career development of the Functional Position of Customs and Excise Inspector at the Directorate General of Customs and Excise (DGCE), East Java I Regional Office, in detail and explore career development problems that exist over time. The framework in this research uses the process flow of career development theory which includes a career planning and career management.